PRRT2 mutations in Japanese patients with benign infantile epilepsy and paroxysmal kinesigenic dyskinesia. (October 2019) - Okumura, Akihisa; Shimojima, Keiko; Kurahashi, Hirokazu; Numoto, Shingo; Shimada, Shino; Ishii, Atsushi; Ohmori, Iori; Takahashi, Satoru; Awaya, Tomonari; Kubota, Tetsuo; Sakakibara, Takafumi; Ishihara, Naoko; et al.
Highlights: PRRT2 mutation is very frequent in familial patients with BIE and/or PKD in Japan. PRRT2 mutation is relatively infrequent in sporadic patients with BIE alone in Japan. The c.649dupC mutation was the most frequent in Japan as well as in other countries. A patients with homozygous c.981C > G mutations showed typical phenotype of BIE and PKD. Abstract: Purpose: This study was performed to clarify the clinical features of Japanese patients with PRRT2 mutations. Methods: The PRRT2 gene was analyzed in 135 patients with benign infantile epilepsy (BIE) or paroxysmal kinesigenic dyskinesia (PKD) using a direct sequencing method: 92 patients had BIE alone, 25 had both BIE and PKD, and 18 had PKD alone. Of the cases, 105 were familial, and 30 were sporadic. Clinical information was collected using a structured questionnaire. Results: PRRT2 mutations were identified in 104 patients. Among the familial cases, PRRT2 mutations were found in at least one individual in 21 of 28 families with BIE alone, in 26 of 27 families with infantile convulsions and choreoathetosis, and in 2 of 3 families with PKD alone. Among the sporadic cases, PRRT2 mutations were observed in 7 of 25 patients with BIE alone, in 1 of 1 patient with BIE and PKD, and in 3 of 4 patients with PKD alone. The c.649dupC mutation was the most frequent, followed by the c.981C > G mutation. Among the patients with epilepsy, the median age at BIE onset was 5 months, the median age at the last seizure was 6 months, and the median number of seizures was 5. Conclusion: PRRT2 mutations were found in 68% of Japanese probands with BIE or PKD. The phenotypes of BIE associated with PRRT2 mutations were consistent with those of BIE diagnosed clinically.